PELATIHAN KEWIRAUSAHAAN DI PONDOK PESANTREN KECAMATAN CARENANG KABUPATEN SERANG - Nafiudin Nafiudin; Muhammad Nurhaula Huddin; Wahyudin Wahyudin (Yayasan Education and Social Center, 2023)
Islamic Boarding School is a type of Islamic education in Indonesia that is traditional and has special characteristics as a place for parents to send their children to school. The spirit and spirit of entrepreneurship in Islamic boarding schools need to be planted as an effort to increase economic resilience. This community service aims to foster an entrepreneurial spirit in the Islamic boarding school in Carenang, namely the Darul Ahibah Islamic Boarding School so that students can be independent in entrepreneurship after graduating from the Islamic Boarding School and contribute to improving the community's economy. The service is carried out from April 09 - April 23, 2022 with 3 approaches including preparation for service including observing service locations, interviewing partner needs, designing service programs and preparing service programs that have been prepared. The next stage is the implementation of the service which consists of entrepreneurship training, the use of waste recycling, and the provision of entrepreneurial stimulus for students. Participants in this service focus on class XII Islamic boarding school students, totaling 48 students. The results of the dedication of students get new knowledge and knowledge and are more confident to try entrepreneurship and form a fund business unit, a good response is also obtained from the Manager Islamic Boarding School who is very appreciative of the service carried out